Exploring Challenges of Piña Growers in the Province of Aklan - Arlene B. De La Cruz (International Journal of Entrepreneurship and Sustainability Studies, 2021)
This study described the challenges experienced by piña growers in the province of Aklan in areas where piña growing, and production activities were declining covering the from 2003 to present. Specifically, this study explored the problems encountered by the piña growers in piña fiber production, their views on the problems encountered and their coping strategies. The study used qualitative research design where phenomenology was used as research method. Data analysis was done using the process developed by Colaizzi’s (1978) as cited by Shosha (2012) to provide assistance in extracting, organizing, and analyzing to explore and understand the challenges encountered by the piña growers. Findings revealed that the piña growers encountered problems such as difficulty in the maintenance and cultivation, longer gestation period, no sustained market and interference of middleman, lack of planting material, natural calamities, infestation, shifting to another variety and lack of support. These resulted to decreased motivation, financial instability, and feeling of neglect but still have the contentment. In order to cope with these challenges, the piña growers turned to problem and emotion-focused strategies where problems are addressed pragmatically. The researcher recommends information dissemination and technology transfer of packaged technologies such as sustainable/sufficient supply of planting material, proper way of cultivation, maintenance, intercropping the SR Pineapple with other crops, improve fruit size and quality, efficient post-harvest handling of piña leaves, develop and improve the present fiber extraction method. It is further recommended that information dissemination should be made among concerned agencies such as the Local Government Units (LGUs), Department of Trade and Industry (DTI), and Department of Agriculture (DA) for appropriate interventions in terms of market price of piña leaves, sustained market demands for piña leaves, and empowered piña growers, leaves processors, knotters and weavers through the formation of a cooperative. Future policies to address the dwindling piña growing activities and piña fiber production may use the proposed theoretical framework for relevant action.